ANALISIS PELANGGARAN ETIKA JURNALISTIK TERHADAP PEMBERITAAN KECELAKAAN PESAWAT AIR ASIA QZ8501 OLEH BREAKING NEWS TV ONE - Dian Esti Nurati, Kemal Al Kahpi & (Transformasi, 2015)
This research was motivated by the rampant criticism made by public on Breaking News TvOne programs, who has violated journalistic ethics, especially in the news Air AsiaQZ8501plane crash edition of30 December 2014 at 14:44 pm.. This research was to identifyand describe a violation of article journalistic ethics by Breaking news News TVOneprograms in the news Air Asia QZ8501plane crashedition of 30 December 2014 at 14:44pm. This study is a qualitative study that is interpretive, in doing research data such as videoand news documents analyzed later confirmed using journalistic ethics and P3 & SPS. Theresults concluded Breaking News TV One edition of 30 December 2014 at 14:44 pm hadviolated article 3 of the Code of Journalistic Ethics, Code of Conduct of Broadcasters Article9, Article 22 paragraph (3) and Article 25 letters a, b, c, and d. Program StandardIndonesian Broadcasting Commission in 2012 Article 9, Article 40, Article 49 and Article 50paragraph d.Key Words: journalism ethics, breaking news tv one, crash air asia